Dualisme Kebijakan Terkait Organisasi Advokat Dalam Putusan Mahkamah Konstitusi No.101/PPU -VII/2009 dan Surat Ketua Mahkamah Agung No.73/KMA/HK.01/IX/2015) - Mukhtarzain, Abdullah Ahmad (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2024)
The single bar association system adopted by Law no. 18 of 2003 concerning Advocates, which was originally used as an organizational legal umbrella that overshadowed or accommodated advocate professions in their recent careers, is currently experiencing polemics regarding legality and also ambiguity about which organization is legitimate, namely between PERADI and KAI, which claim to be legitimate organizations. Therefore it is necessary to review whether the single bar association system needs to be changed to a multi bar association system to meet the needs especially for advocates and prospective advocates so that there is no fighting over rights and authorities as a single advocate organization in Indonesia. This research is a type of normative juridical research or library research, using two approaches, namely the statutory approach and the conceptual approach which are related to the implications of the Constitutional Court Decision No.101/PPU- VII/2009, Letter of Chairman of the Supreme Court No.73/KMA/HK.01/IX/2015 and Law Number 18 of 2003 concerning Advocates related to the change from a single bar association system to a multi bar association using Gustav Radbruch's Theory of Legal Certainty. As for the research results from policy changes related to the single bar association system to become multi bar association in the substance of the revision of Law no. 18 of 2003 concerning Advocates and the Decision of the Constitutional Court No.101/PPU-VII/2009 and Letter of Chief Justice of the Supreme Court No.73/KMA/HK.01/IX/2015 are in accordance with Gustav Radbruch's Theory that the purpose of the change is none other than not to provide benefits (zwech matigheid or doelmatigheid or utility), legal certainty (rechtmatigheid) and achieving justice (gerectigheit) for the advocacy profession, especially for prospective avocados from various organizations to be sworn in after fulfilling the requirements as an advocate. Keywords: Policy Dualism; Single Bars; Multi Bars